El clima organizacional y el desempeño laboral del talento humano de la empresa Expressnet, en la ciudad de Guaranda, provincia Bolívar, año 2023 - Caluña Muguicha, Jhonatan Bladimir (2024)
The objective of this study is to determine how the organizational climate affects the work performance of the human talent of the EXPRESSNET company, taking into account the self-assessment model, considering the great importance that companies, organizations, entities have in terms of having a good both professional and personal relationship between employers and employees, so that there is good performance and development of activities through planned objectives. The research that has been developed is bibliographic and historical, with a quantitative and qualitative approach, carried out with a sample of ten people who make up the company's staff. The main technique used is the survey and interview, and as an instrument the job performance test aimed at staff. For the measurement and interpretation of the results obtained, the nine-box matrix was applied, which helps identify what type of workers the company currently has and the recommendations that are applied to them. In this way, it is obtained that there is a relationship between the organizational climate and work performance, because it guarantees verifying whether the human talent is technically and socially committed to the company, therefore the potential and performance of the employees must be encouraged and recognized. workers this through motivations, talks, bonuses to highlight the skills and abilities of the workers, as long as there is good professional communication.